Peran Orang Tua terhadap Pembelajaran Baca tulis dan Hitung Pada Anak Usia Dini - Ertati, Ertati; Riana, Neti; Kamsi, Nurlila; cici, cici; Afrilina, Sandra (STAI Bumi Silampari, 2025)
This research aims to explore the role of parents in learning calistung in early childhood. This research is descriptive-qualitative with literature study (library research). Research data is in the form of literature and documentation. The findings in this research show that there are three factors supporting the optimization of child development. First, the quality of the parents' self which has an impact on the ability to give birth and educate quality children. Second, caring for children (parenting) parents. Third, consistency and consistency of parents in educating and educating children, especially at an early age. Several roles that can be implemented by parents in optimizing early childhood calistung learning. First, implementing habituation patterns for learning calistung in children. Second, align the home learning model with innovative and interesting play, so that children feel that learning is a fun activity. Third, guiding children by facilitating various kinds of facilities that encourage children's development, such as educational game books and concrete objects.